2015
DOI: 10.1039/c5md00127g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro antiproliferative activity of novel pyrazolo[3,4-d]pyrimidine derivatives

Abstract: A novel series of pyrazoloij3,4-d]pyrimidine derivatives were designed, synthesized and evaluated for their antiproliferative activity. Among the five compounds selected by NCI, compound 11a showed a distinctive pattern of selectivity on cell line panels and was further screened for a 5-log dose range, where it showed potent antiproliferative activity with median growth inhibition (GI 50 ) equal to 1.71 μM against the CNS cancer SNB-75 cell line. The tested derivative showed remarkably the highest cell growth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Structure of the latter was confirmed by the disappearance of the C≡N and NH characteristic absorption bands in the IR spectrum of the starting 5-amino1Hpyrazole-4-carbonitrile 7. Chlorination of compound 8 with phosphorus oxychloride yielded the 4-chloro derivative 9 [19,20]. The latter was allowed to react with different aliphatic and aromatic amines to afford the target pyrazolo [3,4-d]pyrimidin-4-amine derivatives 10 a-e , 11 and 12 (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Structure of the latter was confirmed by the disappearance of the C≡N and NH characteristic absorption bands in the IR spectrum of the starting 5-amino1Hpyrazole-4-carbonitrile 7. Chlorination of compound 8 with phosphorus oxychloride yielded the 4-chloro derivative 9 [19,20]. The latter was allowed to react with different aliphatic and aromatic amines to afford the target pyrazolo [3,4-d]pyrimidin-4-amine derivatives 10 a-e , 11 and 12 (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the presence of a 4-substituted phenyl group (12a-e) in the terminal hydrophobic region demonstrated the most potent anticancer activity, surpassing compounds with an amino group (4), methyl group (7), or various heterocyclic rings, such as 1-H-pyrrole (8), isoindoline (9), indoline (10), and furoyl (11). Among the most active series (12a-e), compound 12b, featuring a 4-fluorophenyl group, exhibited the highest potency, followed by the 4-chlorophenyl derivative 12c.…”
Section: Rsc Medicinal Chemistry Research Articlementioning
confidence: 99%
“…Cancer often exhibits common traits, such as self-proliferation induction, resistance to apoptosis, unlimited proliferative potential, and high invasiveness, which can arise from the hyperactivation of oncogenic pathways and/or disruption of tumor suppressor mechanisms. [4][5][6][7] Protein tyrosine kinases (PTKs) are crucial enzymes that mediate their function by transferring the phosphoryl group from the gamma position of ATP, resulting in the phosphorylation of tyrosine residues in proteins. 8 These enzymes can be categorized based on their location as membrane-bound receptor tyrosine kinases (RTKs) or cytoplasmic non-receptor tyrosine kinases (NRTKs).…”
Section: Introductionmentioning
confidence: 99%
“…[31] Moreover, both the diaryl urea phathalazine (X) and the diaryl urea pyrazolopyrimidine (XI) derivatives showed VEGFR-2 inhibitory activity with IC 50 of 2.5 µM. [38][39][40] Kubo et al, [41] reported the diaryl urea quinoline derivative (XII) which demonstrated a potent VEGFR-2 inhibitory activity in the nanomolar range with IC 50 of 2 nM. The diaryl urea quinazoline derivatives (XIII and XIV) were reported as VEGFR-2 inhibitors with IC 50 of 0.12 and 0.15 µM, respectively.…”
Section: Introductionmentioning
confidence: 99%